Involvement of soilborne Phytophthora species in Central European oak decline and the effect of site factors on the disease - Jung, T.; Blaschke, H.; Oßwald, W. (Plant pathology, 2000)
A survey was made on the occurrence of soilborne Phytophthora species in 35 oak stands on a range of geologically different sites in Bavaria. The most widespread species were P. quercina, P. cambivora and P. citricola. Seven other Phytophthora species were isolated infrequently. The fine root systems of 106 healthy and 111 declining mature trees of Quercus robur and Q. petraea were intensively investigated. The results indicate that, depending on the site conditions, at least two different complex diseases are referred to under the name ‘oak decline’. On sites with a mean soil pH (CaCl2)  3·5 and sandy‐loamy to clayey soil texture Phytophthora spp. were commonly isolated from rhizosphere soil, and highly significant correlations existed between crown transparency and various root parameters. Oaks with P. quercina or other Phytophthora spp. in their rhizosphere had markedly higher levels of fine root damage than oaks without Phytophthora spp., and were subject to a relative risk of severe crown symptoms of 2·1 and 2·8, respectively. In contrast, in stands with sandy to sandy‐loamy soils and a mean soil pH  3·9, Phytophthora spp. were not found. In these stands, correlations between crown transparency and various root parameters were either less significant or not significant. It is concluded that Phytophthora species are strongly involved in oak decline on sandy‐loamy to clayey sites with a mean soil‐pH (CaCl2)  3·5.